2014
DOI: 10.1016/j.atmosres.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of satellite precipitation estimates with reference to a local area in the Mediterranean Sea

Abstract: Precipitation is one of the major variables for many applications and disciplines related to water resources and the geophysical Earth system. Satellite retrieval systems, rain-gauge networks, and radar systems are complementary to each other in terms of their coverage and capability of monitoring precipitation. Satellite-rainfall estimate systems produce data with global coverage that can provide information in areas for which data from other sources are unavailable. Without referring to ground measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 41 publications
7
65
0
3
Order By: Relevance
“…The aforementioned underestimation of CMORPH was in agreement with previous studies (e.g. Abera et al, 2016;Ringard et al, 2015;Lo Conti et al, 2014;Dinku et al, 2010) as well as the acceptable linear correlation (Abera et al, 2016), in particular at monthly timescales. The fact that CMORPH presented the highest underestimation of rainfall for almost all timescales very likely is because CMORPH does not use any observed precipitation data to compute its estimates, in contrast to all the other analysed SREs.…”
Section: How Does the Accuracy Of A Given Sre Change For Different Prsupporting
confidence: 80%
“…The aforementioned underestimation of CMORPH was in agreement with previous studies (e.g. Abera et al, 2016;Ringard et al, 2015;Lo Conti et al, 2014;Dinku et al, 2010) as well as the acceptable linear correlation (Abera et al, 2016), in particular at monthly timescales. The fact that CMORPH presented the highest underestimation of rainfall for almost all timescales very likely is because CMORPH does not use any observed precipitation data to compute its estimates, in contrast to all the other analysed SREs.…”
Section: How Does the Accuracy Of A Given Sre Change For Different Prsupporting
confidence: 80%
“…Lo Conti et al [51] found, however, that the performance of SPPs tends to increase from one to five days and to remain stable at higher temporal aggregation. Estimations from all SPPs were significantly different from observations, at p < 0.05 (Table 3).…”
Section: Evaluation Of Monthly Precipitationmentioning
confidence: 99%
“…Quantitative and systematical precipitation estimations from satellite-based precipitation products have been used in hydrology, climatology, and water-resources management [9][10][11][12][13]. However, it remains a worthy challenge to produce accurate satellite-based precipitation estimations due to the great temporal and spatial variability of the products, acquisitions at different scales, inhomogeneous distributions of rain gauges, complex topography, and cold weather [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%